1966
DOI: 10.3181/00379727-123-31388
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscopic Study of Lipoprotein Production and Release by the Isolated Perfused Rat Liver.

Abstract: above the normal limit, was obtained. The Aminolevulinic acid, porphobilinogen, and other patient, a 54-year-old male with Hgb SC disease and infected leg ulcer, showed 9 total porphyrin values from 4 to 149 pg/24 hr and only one value, 208 pg/24 hr above the normal limit of 180 pg/24 hr.Discussion. Our findings reveal a rather consistent moderate, occasionally marked increase of urinary copro-, total, and uroporphyrins-in this order-and to a slight extent of porphyrin precursors ALA, PBG, and AA during painfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

1969
1969
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 0 publications
4
42
0
1
Order By: Relevance
“…It is further worthwhile noting that lipoprotein formation proceeds whether there is exogenous lipid or not (44), and the synthesis of apoB continues, although at a somewhat reduced rate, even after bile diversion (45). The presence of receptors in villus cells raises the interesting possibility that endogenous cholesterol from LDL contributes, along with exogenous cholesterol and newly synthesized sterol, to the formation of lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is further worthwhile noting that lipoprotein formation proceeds whether there is exogenous lipid or not (44), and the synthesis of apoB continues, although at a somewhat reduced rate, even after bile diversion (45). The presence of receptors in villus cells raises the interesting possibility that endogenous cholesterol from LDL contributes, along with exogenous cholesterol and newly synthesized sterol, to the formation of lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whereas normally oxygen is utilized in the liver primarily for lipid oxidation (40), when ethanol is given, it becomes the main fuel for the liver (41); its oxidation thus supplants that of lipids. Moreover, the endoplasmic reticulum is the site of lipid esterification and lipoprotein production (42,43). It is possible that the proliferation of the smooth endoplasmic reticulum induced by ethanol (44)(45)(46) plays a role in the increased capacity of the alcoholic fatty liver to produce serum lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…This The mechanism of what appears to be an increased capacity to produce lipoproteins after prolonged ethanolfeeding is unknown, but could be linked to the proliferation (23) and increased activity (24) of the hepatic smooth endoplasmic reticulum. Indeed, this structure is the main site of fatty acid esterification (25) and lipoprotein production (26). Furthermore, Joly, Feinman, Ishii, and Lieber (27) have recently shown that chronic ethanol-feeding is associated with increased activity of hepatic L-a-glycerophosphate acyltransferase, a microsomal enzyme involved in fatty acid esterification.…”
Section: Iilillo LI D Ill)mentioning
confidence: 99%